Latest progress in low-intensity pulsed ultrasound for studying exosomes derived from stem/progenitor cells - He, Yi-fang; Wang, Xia-li; Deng, Shuang-ping; Wang, Yan-li; Huang, Qing-qing; Lin, Shu; Lyu, Guo-rong (Frontiers in Endocrinology, 2023)
We wish to re-submit the manuscript titled "Latest progress in low-intensity pulsed ultrasound for studying exosomes derived from stem/progenitor cells " (Manuscript ID：1286900). We thank you and the reviewers for your thoughtful suggestions and insights. The manuscript has benefited from these insightful suggestions. I look forward to working with you and the reviewers to move this manuscript closer to publication in the Frontiers in Endocrinology.The manuscript has been rechecked and the necessary changes have been made in accordance with the reviewers' suggestions. The responses to all comments have been prepared and attached herewith/given below.Thank you for your consideration. I look forward to hearing from you.